Physical activity levels among the adults of Majha region of Punjab, India: A cross‐sectional study. Issue 6 (10th November 2020) - Singh, Harmandeep; Singh, Sukhdev; Singh, Amandeep; Baker, Julien S.
Abstract: Objectives: To construct a physical activity profile of the adult population of the Majha region of the Indian Punjab. Methods: The study included a total of 1130 adult participants aged 18 to 64 years comprising both genders, from rural, urban, and different sociodemographic backgrounds from the four districts of the Majha region of Punjab. The WHO's STEPwise approach to Surveillance instrument for noncommunicable diseases was used to collect data for the selected variables such as physical activity levels, demographic characteristics, behavioral parameters (daily screen time, fruit intake/week, and vegetable intake/week), physical characteristics and self‐reported history of cardiovascular diseases, raised blood pressure, diabetes, and raised cholesterol. The likelihood of physical inactivity was predicted based on independent variables using logistic regression analysis. Results: Overall, 56.81% (95% confidence interval [CI]: 53.9‐59.7) of participants were not sufficiently active as per WHO's moderate‐ to vigorous‐intensity recommendations. Obesity and overweight were observed among 40.2% of the participants. Mean minutes/day of smartphone screen time was 86.11 (CI: 79.48‐92.71). Mean fruit (4.69 CI: 4.42‐4.95) and vegetable (15.35 CI: 15.08‐15.62) weekly consumption was lower than the WHO's recommendations. Work status, residence, annual household income, smartphone screen time, history of raised blood pressure, history of diabetes, and history of raised cholesterol were significant predictors of insufficient physical activity. Conclusions: Our study found a high prevalence of physical inactivity. Being a government employee, being an urban resident, having a middle‐level annual household income, high smartphone screen time and having a history of raised blood pressure, diabetes, and raised cholesterol were all significant predictors of physical inactivity.